Increased Nurse Knowledge Development of Web-Based Geriatric Assessment Application - Ezdha, Awaliyah Ulfah Ayudytha; Fitri, Dwi Elka; Andesa, Khusaeri; Anggreini, Silvia Nora; Hamid, Abdurrahman (Global Health Science Group, 2024)
Nursing care is not only provided to adults but also to the elderly. The elderly require greater assistance in the identification, definition, and resolution of problems that affect them. Increasing life expectancy (UHH) has a complex impact on the welfare of the elderly. Gerontic nurses as the spearhead of nursing services for elderly groups need to get updates and provide information on an ongoing basis related to the mitigation process in elderly groups and other vulnerable groups in an effort to minimize the impact that will occur. Nurses are expected to provide understanding in the form of comprehensive counseling or counseling to the elderly and their families regarding the disease conditions experienced and prevention that can be done at home. So it is important to carry out correct nursing care when the elderly seek treatment at the hospital so that the continuity of services to the home or community can be of higher quality and sustainable. This community service was carried out at Pekanbaru Medical Center Hospital with the aim of improving the quality of nursing care provided to the elderly by developing a web-based assessment and Nursing Care Plan at PMC Hospital. The target of Community Services are 15 nurses who interact with geriatric patients. The results obtained were an increase in nurse knowledge before and after the training. In addition, the nursing care provided becomes more qualified as seen from the documentation carried out by nurses in electronic medical records and the completeness of nursing care. Suggestions for hospitals to continue to be able to develop geriatric Nursing Care Plan in accordance with updated geriatric services in hospitals, conduct socialization with doctors, and collaborate with other health workers (Nutricionis, Physiotherapists, and Psychologists).